Knowledge and practices regarding menstrual hygiene among adolescent girls of rural Nepal - Parajuli, Puspa; Paudel, Narayani; Shrestha, Santoshi (Journal of Kathmandu Medical College, 2017)
Background: Adolescence is a transition period from childhood to adult life during which pubertal development and sexual maturation takes place, thus adolescents have to face physiological development challenges. Adolescent girls often lack knowledge regarding reproductive health including menstrual hygiene which can be due to socio-cultural barriers in which they are grown up.Objective: To assess the knowledge and practices regarding menstrual hygiene among adolescent girls.Methods: A descriptive study was done among one hundred and two adolescent girls of Shree Jansewa Higher Secondary School, Bayarban-8, Morang, where data was collected from the adolescent girls meeting the inclusion criteria.Results: It was found that majority (83.3%) of girls knew that menstruation is a physiological process, 52% knew that it is caused by hormone. More than half of the respondents (53.9%) were taught about menstruation by their mother. Only 33.3% of the respondents used sanitary pad during menstruation. Adolescent girls still have different type of restrictions during menstruation like not being allowed to cook food, not being allowed to visit holy places and sleep in own house during menarche.Conclusion: Socio–cultural restrictions regarding menstruation still persist and knowledge regarding menstrual hygiene among adolescent girls was found to be unsatisfactory. So, the girls should be educated about the process of menstruation, use of proper pads for absorbents and its proper disposal. This can be achieved by giving them proper training and health education by teachers, family members, health educators, and media so that there won’t be any misconception to the adolescent girls regarding menstrual hygiene.Journal of Kathmandu Medical College Vol. 5, No. 1, Issue 15, Jan.-Mar., 2016, page: 23-27